PENGEMBANGAN MODEL BIMBINGAN KARIR SISWA KELAS 1 SMA KOTA MADYA MEDAN DI ERA REVOLUSI INDUSTRI 4.0 - Edidon Hutasuhut; Mirza Irawan; Utami Nurhafsari Putri (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
This study aims to obtain teaching materials or career guidance materials that will be used in school. After conducting the research, it was found that 32 career guidance materials had been provided by BK teachers in SMA Negeri Medan. From this material, research was carried out on 30 alumni of Medan City Public High School. The results show that out of 32 materials, there are 6 materials that are unnecessary. Meanwhile, based on the opinion of 3 BK experts from the 6 materials, it can be used as a material entitled "Regional wealth and its development". Furthermore, to increase the shortage of wasted material in order to meet the number of hours that BK teachers in SMA in general, it is changed to: 1. Appropriate materials are sourced from text books. 2. Suitability between materials and conditions in the field. 3. The method used in conveying the material and media used. 4. Time required. 5. After 5 (five) materials are entered, the results of this study are used as a Career Guidance module.Keywords: Career Guidance Material in Class 1 SMA, Text Books